(untitled) (Annals of Medical Research, 2021)
The widespread use of imaging procedures has led to an increased discovery of incidental masses in the pituitary gland. Although the majority of pituitary incidentalomas are non-functioning benign adenomas but their increased prevalence poses a diagnostic and therapeutic challenge. These masses may cause various hormonal disturbances as well as they might also be a component of multiple endocrine neoplasia syndromes type 1 (MEN-1) or type 4 (MEN-4). In both syndromes, primary hyperparathyroidism frequently accompanies with pituitary adenomas. Herein we present a 56-year-old man with pituitary incidentaloma who is also detected primary hyperparathyroidism. Contrary to our expectations, any gene defects could be found related with neither MEN-1 nor MEN-4 in the genetic examination.